Engaging young learners of English with digital stories: Learning to mean - Lestariyana, Reni Puspitasari Dwi; Widodo, Handoyo Puji (Indonesian journal of applied linguistics, 2018)
Using a digital story to teach English to pupils in primary schools is not a new enterprise in the field of TESOL. However, this learning platform remains under-practiced in Asian primary schools where English is socio-politically viewed as a foreign language. To fill this gap, we implemented digital storytelling (DST) to engage children in the creation of digital stories and in learning to mean in a multimodal way. This article specifically describes our experience of using DST as pedagogical innovation with pupils of 10-12 years old. In this DST project, pupils jointly created digital stories as multimodal texts. In this respect, they utilized different linguistic resources (e.g., Javanese, Bahasa Indonesia, and English) as well as visual and technological affordances, which assisted them in voicing their real-life experience through digital stories. The practical implication of the project is that primary school teachers of English can experiment with DST to engage pupils in meaningful project-based language learning.